cGAS drives noncanonical-inflammasome activation in age-related macular degeneration - Kerur, Nagaraj; Fukuda, Shinichi; Banerjee, Daipayan; Kim, Younghee; Fu, Dongxu; Apicella, Ivana; Varshney, Akhil; Yasuma, Reo; Fowler, Benjamin J; Baghdasaryan, Elmira; Marion, Kenneth M; Huang, Xiwen; et al. (Nature medicine, 2018)
Geographic atrophy is a blinding form of age-related macular degeneration characterized by retinal pigmented epithelium (RPE) death; the RPE also exhibits DICER1 deficiency, resultant accumulation of endogenous Alu-retroelement RNA, and NLRP3-inflammasome activation. How the inflammasome is activated in this untreatable disease is largely unknown. Here we demonstrate that RPE degeneration in human-cell-culture and mouse models is driven by a noncanonical-inflammasome pathway that activates caspase-4 (caspase-11 in mice) and caspase-1, and requires cyclic GMP-AMP synthase (cGAS)-dependent interferon-β production and gasdermin D-dependent interleukin-18 secretion. Decreased DICER1 levels or Alu-RNA accumulation triggers cytosolic escape of mitochondrial DNA, which engages cGAS. Moreover, caspase-4, gasdermin D, interferon-β, and cGAS levels were elevated in the RPE in human eyes with geographic atrophy. Collectively, these data highlight an unexpected role of cGAS in responding to mobile-element transcripts, reveal cGAS-driven interferon signaling as a conduit for mitochondrial-damage-induced inflammasome activation, expand the immune-sensing repertoire of cGAS and caspase-4 to noninfectious human disease, and identify new potential targets for treatment of a major cause of blindness.